3D printing-directed auxetic Kevlar aerogel architectures with multiple functionalization options. Issue 28 (13th July 2020) - Cheng, Qingqing; Liu, Yang; Lyu, Jing; Lu, Qiang; Zhang, Xuetong; Song, Wenhui
Abstract : Nanofibrous Kevlar aerogel metamaterials have been made using cryo-3D printing with special drying techniques at a high resolution and low energy cost. They possess outstanding auxetic mechanical properties with a controlled Poisson's ratio and are multi-functionalisable. Abstract : Auxetic architectures with a negative Poisson's ratio have attracted increasing attention due to their intriguing physical properties and numerous promising applications and recent advancements in manufacturing techniques. However, fabrication of three-dimensional (3D) polymeric auxetic architectures with a tailored hierarchically porous structure and desired physical/mechanical properties remains challenging. Herein, 3D nanofibrous Kevlar aerogel architectures with porosity at multiple scales have been designed and fabricated through a new additive manufacturing strategy, i.e., integration of direct ink writing and freeze-casting with non-toxic solvent-based inks followed by special drying techniques. The highly porous 3D nanofibrous Kevlar aerogel architectures achieve excellent mechanical properties with an ultralow density (down to 11.9 mg cm −3 ) and large specific surface area (up to 350 m 2 g −1 ). The Poisson's ratio is tunable in a wide range, spanning from −0.8 to 0.4, by adjusting the spatial arrangement of the designed pattern struts. Finally, these nanofibrous Kevlar aerogel architectures have been further functionalized into hydrophobic, luminescent and thermoresponsive architectures by using fluorocarbon resin, functional dyes and organic phase-change materials respectively. The multi-functional auxetic aerogel architectures demonstrate potential for a broad range of applications.